Երուսաղէմի հայոց պատրիարքութեան հաւասար իրաւունքների ձեռքբերումը Ս. Ծննդեան եւ Ս. Աստուածածնի տաճարներում 1811—1813 թթ. - Յակոբեան, Տիրան աբղ․ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
История Иерусалимского Армянского Патриархата вместе с братством Свв. Иаковов и армянской общиной является неотъемлемой частью истории самой Армении. Большая часть его истории — это борьба за права на святые места, присутствие в Иерусалиме и Вифлееме. Период предводительства Патриарха Теодороса (Феодора) II Ванеци был полон невзгод. С 1811—1813 гг. до 1818 г. он боролся за восстановление прав армян в Базилике Пресвятой Богородицы, в церкви Пресвятой Девы Марии и Храме Воскресения Господня (Гроба Господня). Впервые мы публикуем его письма и фирман султана Махмуда II с печатью 1811 года и датированной январем 1813 года․ The history of the Armenian Patriarchate of Jerusalem with Sts. James Brotherhood and Armenian community is an inseparable part of the Armenian history with struggles for the rights in the Holy Places and presence in Jerusalem and Bethlehem. The tenure of Patriarch Theodoros of Van was full of hardships. From 1811 to 1813 and until 1818, he struggled to regain the Armenians’ rights in the Basilica of the Nativity and in the Church of Holy Virgin Mary, as well as in the Church of the Holy Sepulchre. His letters, as well as the Firman of Sultan Mahmud II stamped in 1811 and given in January of 1813, will be published for the first time. The decree reaffirms the fact that the Armenians were and are the guardians of the Church of the Holy Sepulchre, as well as the fact that the Copts, Syrians (Jacobites), and Abyssinians (Ethiopians) were followers of the Armenian Church. This firman was an important basis for further struggles in the sanctuaries. Mahmud II reaffirmed it with another decree issued in 1829.
Keywords: Հայոց եկեղեցու պատմություն; Կրօնագիտութիւն